Are cooperators efficiency- or fair-minded?: evidence from a public goods experiment - Maria Vittoria Levati; Matteo Ploner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We use a two-person public goods experiment to distinguish between effciency and fairness as possible motivations for cooperative behavior. Asymmetric marginal per capita returns allow only the high-productivity player to increase group payoffs when contributing positive amounts. Asymmetric contributions, however, yield unequal individual payoffs. To assess a priori cooperative preferences, we measure individual `value-orientations' by means of the decomposed game technique. Overall, our results indicate that fairness (or inequality aversion) is more in°uential than efficiency in driving behavior.
Keywords: A13; C92; D63; H41; 330; Public goods experiments; Conditional cooperation; Fairness; Effciency; Value orientations; Nichtkooperatives Spiel; Öffentliches Gut; Test; Kooperation; Gerechtigkeit; Wirtschaftliche Effizienz